PENGARUH DISIPLIN KERJA DAN KOMUNIKASI ORGANISASI TERHADAP KINERJA KARYAWAN PT.BLUE BIRD CABANG PALEMBANG - Safitri Riski Choiron; Sri Ermeila; Asma Mario (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2022)
This study aims to prove the effect of work discipline and organizational communication on employee performance. This research was conducted at PT. Blue Bird Palembang Branch. The data used in this study are primary and secondary data obtained from questionnaires distributed to respondents. The data that was successfully collected were 61 respondents from 61 questionnaires that were distributed. The media used to analyze is by using SPSS for windows version 23. The test is carried out in several stages, namely validity and reliability tests, classical assumption tests and hypothesis testing. The results of this study indicate that the coefficient of determination (R2) is 0.951 or 95.1 % and the remaining 4.9% is influenced by other variables not analyzed in this study. So it can be concluded that work discipline and organizational communication have an effect on employee performance. The object that is taken in this research is PT. Blue Bird Palembang Branch. The data analyzed were work discipline and organizational communication on employee performance. The purpose of this research is to determine the performance of the employees of PT. Blue Bird Palembang Branch and how much influence the work discipline and organizational communication have on employee performance at PT. Blue Bird. The method of analysis used in this research is quantitative descriptive method and qualitative descriptive method.